STUDI POTENSI PERTANIAN “KAKI“ LAWU SELATAN WILAYAH WONOGIRI - Arief Budi Nugroho; Eko Murniyanto (Agrovigor, 2014)
Agricultural potential have the highest contribution to Gross Domestic Product Wonogiri (BPS, 2011) because it is proper database agricultural potential is necessary for basic agricultural development planning in particular and the economy in general. In turn can be achieved high revenue. This study aims to provide information on the potential of agriculture in the "Kaki Lawu Selatan" South and provide recommendations on the development of agricultural. From this study the South Lawu Foot Zone can be divided into 4 (four) zones: the upper leg, foot zone central zone, lower leg and foot slope zone. Among these zones, based on the parent material foot zone less potential for commercial agriculture, based on the value of LQ, three priority commodities suspected potential for the avocado fruit, rambutan, breadfruit. Vegetables garlic, carrots and cabbage. Plantation commodities include coffee, cocoa and tobacco / patchouli. Food commodities include cassava, maize and peanuts.Kata kunci : Agricultural potential